Investigation of Smart Home Energy Management System for Demand Response Application - Ma, Yunlong; Chen, Xiao; Wang, Liming; Yang, Jianlan (Frontiers in Energy Research, 2021)
Electricity market reform provides the conditions for demand-side load resources to be incorporated into the supply–demand regulation, and the increase of residential-side electrification level makes residential load resources a high-quality resource for demand response (DR). Resident home appliances participate in the “two-way interaction” of the power grid in the form of DR, which can effectively alleviate the tension of power supply and consume clean energy, to improve the safe and stable operation of the power system. Firstly, this article summarizes the structure and functions of the home energy management system (HEMS). Secondly, it discusses the key technologies of the HEMS, starting from an advanced metering infrastructure (AMI) and DR technology. Finally, it analyzes the control strategies of the HEMS, including component models and various optimal scheduling algorithms, and describes the challenges of the HEMS.